An Iterative Algorithm for the Coefficient Inverse Problem of Differential Equations (Journal of Computational Mathematics, 2021)
In this paper, an iterative algorithm for solving a coefficient inverse problem is submitted. The key of the method is to project an unknown coefficient function on a finite dimensional function space. Thus, the inverse problem can be changed into a nonlinear algebraic system of equations.